An Automated Python Algorithm to Quantify ZDR Arc and KDP–ZDR Separation Signatures in Supercells - Wilson, Matthew B.; Van Den Broeke, Matthew S. (Journal of atmospheric and oceanic technology, 2021)
Supercell thunderstorms often have pronounced signatures of hydrometeor size sorting within their forward-flank regions, including an arc-shaped region of high differential reflectivity ( Z DR ) along the inflow edge of the forward flank known as the Z DR arc and a clear horizontal separation between this area of high Z DR values and an area of enhanced K DP values deeper into the storm core. Recent work has indicated that Z DR arc and K DP – Z DR separation signatures in supercell storms may be related to environmental storm-relative helicity and low-level shear. Thus, characteristics of these signatures may be helpful to indicate whether a given storm is likely to produce a tornado. Although Z DR arc and K DP – Z DR separation signatures are typically easy to qualitatively identify in dual-polarization radar fields, quantifying their characteristics can be time-consuming and makes research into these signatures and their potential operational applications challenging. To address this problem, this paper introduces an automated Python algorithm to objectively identify and track these signatures in Weather Surveillance Radar-1988 Doppler (WSR-88D) data and quantify their characteristics. This paper will discuss the development of the algorithm, demonstrate its performance through comparisons with manually generated time series of Z DR arc and K DP – Z DR separation signature characteristics, and briefly explore potential uses of this algorithm in research and operations.